Mathematics Teacher Preparation in Central America and the Caribbean The Cases of Colombia, Costa Rica, the Dominican Republic and Venezuela - Ruiz, Angel (SpringerBriefs in Education, 2017)
*THIS BOOK WILL SOON BECOME AVAILABLE AS OPEN ACCESS BOOK* This book is an excellent synthesis of the initial and continuing preparation for Mathematics Teaching in Colombia, Costa Rica, Dominican Republic and Venezuela, from which comparative analyses can be made that show similarities and differences, and highlight various perspectives. In August 2012, a workshop of the Capacity and Networking Project (CANP) of the International Commission on Mathematical Instruction (ICMI) was held in Costa Rica. This CANP brought together for two weeks a group of 66 Mathematics educators, mathematicians, university administrators, and elementary and secondary teachers from Colombia, Venezuela, the Dominican Republic, Panamá and Costa Rica. The goal was to promote progress in Mathematics Education in the region; as such it was a unique experience in the region. One of the most important results of this event was the creation of the Mathematics Education Network of Central America and the Caribbean (REDUMATE). It was organized by persons associated with the Mathematics Education Reform Project in Costa Rica (responsible for the most outstanding and innovative curriculum reform in Latin America) and the Inter-American Committee on Mathematics Education (IACME), which is an official regional multinational organization affiliate of ICMI. This book brings to the international Educational Community an important collection of experiences and ideas in the Mathematics Education of four countries of a region within the heart of the American continent, a region that has been many times forgotten. The dissemination of these results can promote the search for international collaborative actions in a wider scale.